2017
DOI: 10.1016/j.enzmictec.2016.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Mediator-free interaction of glucose oxidase, as model enzyme for immobilization, with Al-doped and undoped ZnO thin films laser-deposited on polycarbonate supports

Abstract: Research Highlights: Electrochemical interaction of ZnO and AZO thin films with the enzyme glucose oxidase was studied.  Nature of interaction of GOx with AZO was explored using XPS.  Mechanism of the electron transfer between GOx and AZO/ZnO was studied using EIS.  The results show that AZO is preferable to ZnO for GOx immobilization and glucose sensor development. Abstract:Al doped and undoped ZnO thin films were deposited by pulsed-laser deposition on polycarbonate sheets. The films were characterized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 47 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…The concentration of H 2 O 2 was calculated using the following equation where ε is the molar extinction coefficient of 4-AAP at 505 nm and equals 12.88 mM –1 cm –1 , L is the effective width of the cuvette used, and the factor 1/2 corresponds to the 2 mol of H 2 O 2 required to reduce 1 mol of 4-AAP …”
Section: Methodsmentioning
confidence: 99%
“…The concentration of H 2 O 2 was calculated using the following equation where ε is the molar extinction coefficient of 4-AAP at 505 nm and equals 12.88 mM –1 cm –1 , L is the effective width of the cuvette used, and the factor 1/2 corresponds to the 2 mol of H 2 O 2 required to reduce 1 mol of 4-AAP …”
Section: Methodsmentioning
confidence: 99%
“…As shown in Table 1 , the detection limits of the ZnO-Ag-based glucose sensors are slightly smaller than those reported in the literature [ 13 , 14 , 17 ], whilst the linear ranges are close to the corresponding values. Whereas the sensitivities of the ZnO-Ag-based glucose sensors approach that of the ZnO-Al-based one, they are much smaller than that of the ZnO-Ni- and ZnO-Co-based ones.…”
Section: Resultsmentioning
confidence: 49%
“…[ 12 , 13 , 14 ] or excellent conductivity (such as Au, C, and Al, etc.) [ 15 , 16 , 17 ]. For example, Anusha coated Pt nanoparticles on ZnO nanoporous structures, and confirmed that the Pt nanoparticles enhance both the catalytic activity and electron transfer ability of the glucose sensor [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation